Konsep Spiritual Teaching dalam Perspektif Hadis - Purwasetiawatik, Titin Florentina; Ahmad, La Ode Ismail; Amri, Muhammad (Jurnal Diskursus Islam, 2023)
Spiritual education in the context of Islamic education is an effort to mature the souls of students on the journey towards closeness to Allah SWT. In various scientific references, spiritual teaching is changing students from a dirty soul to a clean soul, from reasoning that has not submitted to Allah to reasoning that obeys the Shari’ah, from a hard and rusty heart to a soft and clear heart. Change from spirituality that is far from awareness of Allah SWT, negligent in worshiping and lacking sincerity in doing it towards spirituality that is ma’rifat towards Allah SWT. and always serve Him sincerely, from a body that does not obey the rules of the Shari’a to becoming a body that always adheres to the rules of the Shari’a of Allah SWT. Abstrak Pendidikan spiritual dalam konteks Pendidikan Islam adalah upaya pendewasaan jiwa peserta didik dalam perjalanan menuju kedekatan dengan Allah swt. Dalam berbagai referensi ilmiah, spiritual teaching adalah merubah peserta didik dari jiwa yang kotor menuju jiwa yang bersih, dari nalar yang belum tunduk kepada Allah menuju nalar yang patuh kepada syari’at, dari hati keras dan berkarat menuju hati yang lembut dan jernih. Merubah dari Rohani yang jauh dari kesadaran Allah swt., lalai dalam beribadah dan kurang ikhlas melakukannya menuju Rohani yang ma’rifat kepada Allah swt. dan senantiasa berbakti kepada-Nya dengan tulus, dari tubuh yang kurang mentaati aturan syari’at menuju menjadi tubuh yang senantiasa memegang aturan-aturan syari’at Allah swt.